The Impact of Social Media Campaigns on Reducing Plastic Waste in Thailand’s Coastal Areas - Ananda Jirasit (Studies in Social Science & Humanities, 2024)
This paper examines the role of social media campaigns in reducing plastic waste in Thailand’s coastal areas, focusing on their impact on public behavior and attitudes. Through campaigns such as #BeatPlasticPollution, #NoMorePlastic, and #TrashHeroThailand, social media has become a powerful tool for mobilizing communities and promoting sustainable practices. These campaigns have significantly influenced the reduction of single-use plastics, increased recycling efforts, and broader participation in environmental clean-up activities. By engaging local stakeholders, including coastal communities, businesses, and government entities, these initiatives have fostered a collective movement toward sustainability. The analysis explores how social media has reshaped public perceptions of plastic pollution and its environmental consequences, comparing behavior and awareness before and after key social media campaigns. The findings underscore the critical role of digital platforms in environmental advocacy and their long-term potential to drive behavior change on a global scale.